Analisis Variography pada Estimasi Ordinary Kriging Endapan Batubara Di Kecamatan Murung Pudak, Kabupaten Tabalong, Provinsi Kalimantan Selatan - Vina Wulandari; Romla Noor Hakim; Hafidz Noor Fikri (Universitas Muslim Indonesia, 2020)
A functional analysis of the determination of the variogram value is very influential on the coal model formed (variography analysis). Variography is a series of activities ranging from data searching, modeling to analysis reports. Coal quality estimation is an activity to get a proper distribution of coal quality values, and the results can contribute as one of the control processes in coal mining activities. This research aims to estimate coal parameters (Ash Content, Calorific Value, Total Moisture, and Total Sulfur) using Ordinary Kriging. Comparison of Ordinary Kriging estimation variogram model with omnidirectional and omnidirectional-vertical model variogram results in the conclusion that the vertical variogram is quite capable of giving a positive effect on the Ordinary Kriging estimation results seen from the residual value of the results of cross-validation, although in general, the distribution of Ordinary Kriging results is not too much different.